2020
DOI: 10.1002/qua.26341
|View full text |Cite
|
Sign up to set email alerts
|

Engaging undergraduate students in computational chemistry research: A tutorial for new assistant professors

Abstract: In this article, we provide advice and insights, based on our own experiences, for computational chemists who are beginning new tenure-track positions at primarily undergraduate institutions. Each of us followed different routes to obtain our tenuretrack positions, but we all experienced similar challenges when getting started in our new position. In this article, we discuss our approaches to seven areas that we all found important for engaging undergraduate students in our computational chemistry research, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Sabatini, 1997). Previous studies have shown that the instructors have tried different strategies (Ball et al, 2020) to enhance the research experience of undergraduate students by designing suitable research assignments as a course project. Moreover, a survey of old literature reveals that the undergraduate research activities undertaken are through summer internship projects (Houser & Lemmons, 2018), course project/term projects (Amekudzi et al, 2010;Ford & Newmark, 2011;Ponce et al, 2021), or some kind of special research program organized involving undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…Sabatini, 1997). Previous studies have shown that the instructors have tried different strategies (Ball et al, 2020) to enhance the research experience of undergraduate students by designing suitable research assignments as a course project. Moreover, a survey of old literature reveals that the undergraduate research activities undertaken are through summer internship projects (Houser & Lemmons, 2018), course project/term projects (Amekudzi et al, 2010;Ford & Newmark, 2011;Ponce et al, 2021), or some kind of special research program organized involving undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, they discuss their approaches to seven areas that they found were critical for engaging undergraduate students in computational chemistry research, including setting up computational resources, recruiting research students, training research students, designing student projects, managing the lab, mentoring students, and student conference participation. [9] The second perspective is by Mauricio Cafiero and three of his alumnae. A longtime faculty member at Rhodes College, Cafiero and his former students describe how the culture of the Cafiero group empowered undergraduate women in computational chemistry.…”
mentioning
confidence: 99%